(untitled) (Bangladesh Journal of Animal Science, 2012)
One hundred eighty straight run day old Cobb-500 broilers were reared on rice husk, sawdust, wood shaving and chopped tea leaves litter up to 35 days of age. The broilers were fed ad libitum. At 35 days the body weight of chicken reared on sawdust attained the highest body weight (p<0.01) than other litters. FCR was the best on saw dust. The moisture content of different litters did not differ significantly. Oocyst population in rice husk was found to be higher (p<0.01) than those on other litters, except those reared on wood shaving. Moisture content of litters and oocyst population were positively correlated at 14 and 35 days and negatively correlated at 21 and 28 days of age. The litter cost per broiler and per kg broiler was the highest on rice husk (RH), intermediate on sawdust (SD), Wood shavings (WS) and the lowest on chopped fallen tea leaves (CFTL). It was concluded that it may be possible to minimize the cost of litter by using CFTL. http://dx.doi.org/10.3329/bjas.v41i1.11978